Employment status and information needs of patients with breast cancer: a multicentre cross-sectional study of first oncology consultations. Issue 9 (29th September 2020) - Mazzi, Maria Angela; Perlini, Cinzia; Deledda, Giuseppe; Ghilardi, Alberto; Buizza, Chiara; Bottacini, Alessandro; Goss, Claudia; Del Piccolo, Lidia
Abstract : Objectives: To investigate the early information needs of women with a recent diagnosis of breast cancer (BC) according to their employment status. Design: Cross-sectional. Setting: Secondary-care patients attending three outpatient oncology clinics in northern Italy. Participants: 377 women with a recent diagnosis of early-stage, non-metastatic BC aged 18–75 were recruited. Of them, 164 were employed, 103 non-employed and 110 retired. Outcome measures: The first consultation visit with an oncologist was audio-recorded and analysed for the number and type of questions asked. Linear regression models considering consultations' and patients' characteristics as confounding variables were applied. Results: Employed patients asked significantly more questions than non-employed and retired patients (17 vs 13 and 14; F=6.04; p<0.01). When age and education were included in the statistical model, the significance of employment status was rearranged among all the variables and was no more significant (b=1.2, p=0.44). Employed women asked more questions concerning disease prognosis (0.7 vs 0.4 and 0.6; F=3.5; p=0.03), prevention (1.4 vs 0.6 and 0.7; F=10.7; p<0.01), illness management (7.2 vs 6 and 5.4; F=3.8; p=0.02) and social functioning (37% vs 18% and 20%; χ 2 =14.3; p<0.01) compared with the other two groups. Finally, they attended more frequently the consultation alone (37% vs 18% and 25%; χ 2 =10.90, p<0.01), were younger (50 vs 58 and 67 years; F=63.8; p<0.01) and with a higher level of education (77% vs 27% and 45%; χ 2 =68.2; p<0.01). Conclusions: Employment status is related to the type of questions asked during the first consultation. Also, it interrelates with other patients' characteristics like age and education in determining the number of questions asked. Patients' characteristics including employment status could be considered in tailoring work and social-related information provided during the first oncological consultation. Future studies could explore potential differences in information needs according to the different kinds of work.